Molecular-matched materials for anticancer drug delivery and imaging. (October 2015) - Wang, Dun; Fu, Qiang; Tang, Jingling; Hackett, Michael; Wang, Yongjun; Liu, Feng
Aim: In this study, we aim to construct nanoformulation with high-cargo loading and controlled serum kinetics.Materials & methods: Molecular-matched materials (MMMs) are established through the conjugation of the functional moiety to a molecule representative of the nanoparticle's core. Molecular-matched nanoemulsions and liposomes were prepared using MMMs.Results: This technique based on MMMs even allows us to efficiently load either hydrophobic or hydrophilic moieties into a hydrophobic core of the nanoparticles. MMMs-based nanoparticles showed marked improvement in serum pharmacokinetics and anticancer effect.Conclusion: The desired performance can be achieved when the hydrophobic anchor of the PEG derivatives and the moiety conjugated to the therapeutic (or imaging) agents are molecularly identical to the core.